RP-HPLC determination of Furosine in fermented milk of different brands retailed in China - Mekonen Tekliye; Xu Pei; Mingsheng Dong (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
Heat treatment of milk is the most widely used processing technology in the dairy industry. It results in many chemical and biochemical changes in milk, the extent of which depends on the temperature-time combinations, the heating method utilized, and milk pre-treatment conditions [1-3]. The principal categories of treatment methods used for milk for direct consumption and those used for specifi c dairy products are in-container sterilization, UHT, ESL processing, and pasteurization [4,5].